Peranan dan sumbangan himpunan Mahasiswa Islam Cawangan Salatiga, Indonesia dalam pembaharuan Islam: Kajian dari tahun 1985-2015 / Kastolani - Kastolani, - (2017)
This research entitled “ The Role and Contribution of the Islamic Students Association Salatiga, Indonesia Baranch in Islamic Revival: An Analysis from 1985-2015” . Among the aims of this research is to analyze the thought and cadre activities of HMI Salatiga which have contributed to the Islamic reform movement. This study is a combination of library research with field research to describe the movement of Islamic reform in HMI Salatiga. Library research aims to analyze the thoughts of Islam in modernism perspective, and the field research uses resource mobilization theory which is aimed to analyze the strategies and implimentation of HMI cadre development, roles, and contributions of HMI in the Islamic reform. The findings of this research are as follows, 1) the characters of HMI Islamic thought are substantial, transformative and modern; 2) Religious discussions and any format of cadre trainings have been succeded to develop human capital of HMI cadres to become activist of Islamic reform; 3) The role and contribution of HMI is significant to develop intellectual generation who have a clear vision religious and adapting to the national aspiration. The fundamental factors of supporting Islamic reform sustanbility is reinforcing the resources of morality, cultural, material and human capital. The moral resource (Islamic thought) and human capital (alumni network) are the main supporter for the sustainability of the Islamic reform movement.